Electric resistivity of fine chromite ore: measurement and prediction. (April 2013) - Pan, C; Lv, X W; Bai, C G; Liu, X Y; Li, D H
Abstract : Fine chromite ore is a common raw material used to produce ferrochrome alloy by submerged electric arc furnace process. The electric resistivity of fine chromite ore determines current distribution, which in turn, affects operation efficiency during the process. The effects of particle size and contact area of the particles on the electric resistivity of several types of chromite were investigated at room temperature. The relationship between the electric resistivity of mixed particles and the volume fraction of lump ore to fine ore was also studied. Contact resistivity decreases with increasing box-counting dimension. Finally, a 'parallel connection circuit model' for predicting the electric resistivity of the chromite mixture was developed. Results show that electric resistivity increases as particle size increases, and that the electric resistivity of the mixture decreases with increasing volume ratio of fine ore. The electric resistivity calculated by the parallel connection circuit model is consistent with measurements. Le minerai fin de chromite est un matériau brut commun utilisé dans la production d'alliage de ferrochrome par le procédé du four électrique à arc submergé. La résistivité électrique du minerai fin de chromite détermine la distribution du courant, qui, à son tour, affecte l'efficacité de l'opération lors du procédé. On a examiné, à la température de la pièce, l'effet de la taille de particule et de l'aire de contact des particules sur la résistivité électrique de plusieurs types de chromite. On a également étudié la relation entre la résistivité électrique de particules mélangées et la fraction volumique du minerai en bloc par rapport au minerai fin. La résistivité par contact diminuait avec une augmentation de la dimension de boîtes. Finalement, on a développé un ″modèle de circuit à connexions en parallèle″ pour la prédiction de la résistivité électrique du mélange de chromites. Les résultats montrent que la résistivité électrique augmente avec une augmentation de la taille de particule et que la résistivité électrique du mélange diminue avec une augmentation de la densité relative de minerai fin. La résistivité électrique calculée au moyen du modèle de circuit à connexions en parallèle est en accord avec les mesures.